2016
DOI: 10.1021/acs.jpcc.6b00456
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Crotonaldehyde over Ir–FeOx/SiO2 Catalysts: Enhancement of Reactivity and Stability by Ir–FeOx Interaction

Abstract: A series of FeO x -promoted Ir/SiO2 catalysts were prepared and tested for gas phase selective hydrogenation of crotonaldehyde. It was found that a catalyst containing Ir nanoparticles contacting with highly dispersed FeO x clusters (3Ir/0.1Fe/SiO2) showed excellent activity and stability, with a 5-fold enhanced steady state crotyl alcohol yield (59.6%) compared to that of the bare Ir/SiO2 (12.4%), while a catalyst promoted with high content of Fe (3Ir/3.5Fe/SiO2) had high initial activity but deactivated rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…For example, Tamura et al [22] reported that the addition of various promoters such as ReO x , MoO x , FeO x and NbO x significantly enhanced the activity of the Ir/SiO 2 catalyst. On a NbO x -promoted Ir/SiO 2 catalyst (with an Ir/Nb molar ratio of 2/1), the CRAL conversion (41.6%) was six-fold higher than that of the bare Ir/SiO 2 (7.3%), and the turnover frequency (TOF) on the NbO x -promoted Ir catalyst was as high as 0.21 s −1 at 80 • C. Similar findings were also reported in our previous works [18,23,24].…”
Section: Scheme 1 the Hydrogenation Reaction Routes Of Crotonaldehyde (Cral)supporting
confidence: 89%
See 1 more Smart Citation
“…For example, Tamura et al [22] reported that the addition of various promoters such as ReO x , MoO x , FeO x and NbO x significantly enhanced the activity of the Ir/SiO 2 catalyst. On a NbO x -promoted Ir/SiO 2 catalyst (with an Ir/Nb molar ratio of 2/1), the CRAL conversion (41.6%) was six-fold higher than that of the bare Ir/SiO 2 (7.3%), and the turnover frequency (TOF) on the NbO x -promoted Ir catalyst was as high as 0.21 s −1 at 80 • C. Similar findings were also reported in our previous works [18,23,24].…”
Section: Scheme 1 the Hydrogenation Reaction Routes Of Crotonaldehyde (Cral)supporting
confidence: 89%
“…Concerning the turnover frequency for the CROL formation, the values obtained on the Ir/TiO 2 catalysts in the current works (2.6-4.4 × 10 −3 s −1 ) are comparable to those on bare supports (e.g., 3.8 × 10 −3 s −1 on the Ir/TiO 2 [13]). However, they are lower than those obtained on the promoted Ir catalysts (e.g., 16.9 × 10 −3 s −1 on the 3Ir-0.05(Cr-Fe)/SiO 2 [18] and 18.0 × 10 −3 s −1 on the 3Ir/0.1Fe/SiO 2 [23]), which could be ascribed to the much higher Ir dispersions in the current work (64.7-84.6%, Table 1) than those in 3Ir-0.05(Cr-Fe)/SiO 2 (29.0%) [18] and 3Ir0.1Fe/SiO 2 (23.5%) [23]. a All these catalysts were applied in the gas-phase hydrogenation of crotonaldehyde.…”
Section: Catalytic Behaviors Of the Catalystsmentioning
confidence: 64%
“…Pt-based catalysts such as Pt/Ga 2 O 3 , Pt/CeO 2 , and Pt-Sn/SiO 2 and Ru-based catalysts such as Ru/ZnO, Ru-Ir/ZnO, and so on were reported. It should be noted that Ir metal is more effective component than other noble metals on the basis of the previous reports such as Ir/Ga 2 O 3 , Ir-FeO x /SiO 2 , Ir-CrO x /SiO 2 , and so on. Various kinds of catalysts were proposed and developed; however, high-yield synthesis of crotyl alcohol in gas-phase reaction seems to be difficult in comparison with the liquid-phase reaction, and the reported highest yield was 81%, which was obtained by using bimetallic Ru-Ir/ZnO catalyst (Table S1). Moreover, the catalytic activities are low (formation rate of crotyl alcohol typically <30 μmol·g metal –1 ·s –1 ), and it is difficult to achieve both high activity and high yield simultaneously (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…in the process, and it has disadvantages such as high cost, harsh reaction conditions, contaminate generation, and challenges in product separation. The new catalytic hydrogenation method has been drawing attention due to its low cost and environmental friendly nature. , The possible hydrogenation products of crotonaldehyde (CDE) include crotonyl alcohol (COL), butyraldehyde (BDE), ENOL, and butanol (BOL), which means there is competition for the hydrogenation on different double bonds. The bonding energy of CC is around 615.0 kJ/mol and for CO it is about 715.0 kJ/mol, which makes the hydrogenation reaction favor the CC bond; at the same time the conjugation effect will enhance this trend. Therefore, the synthesis of high reactivity and selectivity catalyst that favors CO hydrogenation is very challenging …”
Section: Introductionmentioning
confidence: 99%